Penampilan Morfologis Galur-Galur Harapan Kedelai Hasil Persilangan Varietas Malabar dan Kipas Putih - Nugroho, Amin; Suryati, Dotti; Chozin, Mohammad (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2015)
The increasing demand for soybean is driven by population growth and development of industry. The current import of soybean should be considered as pragmatic solution to fill the gap between supply and demand. In the long term, the domestic production of soybean has to be increased to minimize the dependency on imported soybean. As part of soybean breeding program for yield improvement, this study was undertaken to evaluate the performances of five elite lines (11 AB, 13 ED, 14 DD, 19 BE, and 25 EC) derived from cross of Malabar and Kipas Putih as compared to their parental varieties and Tanggamus (commercial variety). The evaluation was set up in a completely randomized block design with three replications. Significant variations among the genotypes were found on plant height, flowering date, number of fertile node, hundred seed weight, plant biomass, and protein and lipid contents, but not on number of productive branch, maturity date, pod number, yield per plant, and yield per plot. In most cases, the evaluated lines had intermediary performances between their parental varieties, although some lines produced earlier flowering, larger seed, higher protein content, and lower lipid content. 11 AB exhibited a superiority over its parental and Tanggamus in term of plant biomass and protein content.